Pengaruh Model Pembelajaran Teams Games Tournament (TGT) Berbantuan Media Monopoli Matematika (MONIKA) Terhadap Kemampuan Menghitung Keliling Dan Luas Bangun DatarKEMAMPUAN MENGHITUNG KELILING DAN LUAS BANGUN DATA - Mei Puspitasari (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the Teams Games Tournamentlearning model assisted by the Mathematical Monopoly (MONIKA) media on theability to calculate the perimeter and area of flat shapes for fourth grade students.This research is a type of Pre-Experimental Design research, with the OneGroup Pretest-Posttest Design model. The samples taken were 20 students who wereused as the experimental class. The sampling technique used was saturatedsampling. Data collection using the test method. This test is used to measure theextent to which students are able to calculate the circumference and area of flatshapes before and after being given treatment. The analysis used in this study is theWilcoxon Signed Rank Test with the SPSS version 25.0 program.The results showed that the Teams Games Tournament learning modelassisted by the Mathematical Monopoly (MONIKA) media had an effect on the abilityto calculate the circumference and area of flat shapes. Evidence of an increase instudents' ability to calculate the circumference and area of flat shapes is that thereis a significant difference between the pretest and posttest scores, namely the pretestaverage value of 50.88, while the posttest average value of 70.55. This is supportedby the existence of a hypothesis test carried out with the Wilcoxon Signed Rank Test,the Asymp. Sig. (2-tailed) of 0.000 (0.000 < 0.005). Based on the results of the analysisand discussion, there was an increase of 19.67 from the average pretest and posttestresults. The results of the study can be concluded that the use of the Teams GamesTournament learning model assisted by the Mathematical Monopoly (MONIKA)media has a significant effect on the ability to calculate the circumference and areaof flat shapes.